MODERATING ROLE OF ORGANIZATIONAL STRUCTURE ON THE RELATIONSHIP BETWEEN LEADERSHIP STYLES AND DIGITAL CULTURE ADOPTION (Malaysian Management Journal, 2025)
This study explores the complex interplay dynamics between leadership styles, organizational structure, and digital culture adoption within Katsina State Ministries, Departments and Agencies (MDAs), with particular emphasis on how these elements influence digital transformation efforts. Data were collected from 630 employees across four randomly selected MDAs—Katsina State Library Board, State House of Assembly, Ministry of Agriculture and Livestock Development, and Katsina State Television Authority. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed for data analysis. The findings reveal a significant positive relationship between transformational leadership style and digital culture adoption, as well as a significant but negative relationship between transactional leadership style and digital culture adoption. However, the analysis did not reveal any significant moderating effects of organizational structure on these relationships. While the study provides valuable insights, limitations such as the use of cross-sectional data and the limited generalizability of the findings should be noted. The results underscore the critical role of leadership—particularly transformational leadership—in driving digital culture adoption. Based on these findings, the study recommends that organizations invest in leadership development programs that promote transformational leadership behaviors and foster a culture of digital innovation. Additionally, future research should consider longitudinal or experimental designs, employ multi-source data collection methods, and explore other organizational contexts to enhance the robustness and applicability of the findings. Further investigations into the mechanisms and long-term impacts of leadership and structural reforms are also encouraged to provide actionable guidance for organizations navigating digital transformation in today’s evolving landscape.